2016
DOI: 10.1159/000450854
|View full text |Cite
|
Sign up to set email alerts
|

Excess Body Weight during Childhood and Adolescence Is Associated with the Risk of Multiple Sclerosis: A Meta-Analysis

Abstract: Background and Aim: Several epidemiological studies have reported the association between obesity and multiple sclerosis (MS). Methods: A literature search of the observational studies, published as original articles in English before December 2015, was performed using electronic databases. Results: Five observational studies were included, of which 3 were case-control studies and 2 were cohort studies. The pooled relative risk (RR) for overweight and obesity during childhood and adolescence compared with norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 25 publications
2
23
0
2
Order By: Relevance
“…Findings for fe-male patients matched those in the literature, which indicated that obesity has consistently been associated with a 1.6 to 2.4 increase in MS risk, but the degree of male risk has been disputed. [9][10][11]14,16,26 Most adult studies have shown either no risk or only attenuated risk in males. 10,11,13,16,36 Pediatric findings are scarce, but a study has also reported statistically significant male risk (n = 59; BMI>85th percentile; OR, 1.43; P = .01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings for fe-male patients matched those in the literature, which indicated that obesity has consistently been associated with a 1.6 to 2.4 increase in MS risk, but the degree of male risk has been disputed. [9][10][11]14,16,26 Most adult studies have shown either no risk or only attenuated risk in males. 10,11,13,16,36 Pediatric findings are scarce, but a study has also reported statistically significant male risk (n = 59; BMI>85th percentile; OR, 1.43; P = .01).…”
Section: Discussionmentioning
confidence: 99%
“…These results have since been validated in other adult studies, with a growing body of evidence indicating that a high BMI in adolescence and possibly in early life increases MS risk. [10][11][12][13][14][15][16][17][18] This association is evident even after controlling for established genetic and environmental risk factors and has been described in both sexes, although a stronger association has been repeatedly shown in females. 16 The exact underlying pathologic mechanisms still require elucidation, but lower serum vitamin D levels, altered adipokine profiles favoring a proinflammatory state, deregulated gut microbiota, unfavorable interaction with HLA-risk genes in puberty, and earlier start of menses have all been suggested to play a role in obesity-associated MS risk.…”
mentioning
confidence: 99%
“…Several high quality observational studies have reported that obesity in adolescence and early adulthood is associated with approximately double the risk of developing pediatric and adult MS compared with normal‐weight individuals . The association has been largely confirmed in females, including a dose‐effect, while evidence is mixed regarding the association in males …”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%
“…Environmental factors are of 2 types: a) of nondietetic origin: 1) viral infections (no association with Epstein-Barr virus was established in the BENEFIT study [4]); 2) heavy metal poisoning [5]; 3) cigarette smoke (no association with tobacco was Electronic supplementary material The online version of this article (https://doi.org/10.1007/s13311-017-0581-4) contains supplementary material, which is available to authorized users. established in the BENEFIT study [4]); b) associated with dietary habits and metabolic conditions: 1) excess body weight in childhood and adolescence [6,7]; 2) low vitamin D status [8,9]; 3) sedentary lifestyle and high-animal-fat/highsugar Western diets [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%